Holding Power of Orthopaedic Screws in Bovine Femoral Heads. A Comparison of Three Cannulated Screws - Wilson, D. G.; McCabe, R. P. (Veterinary and Comparative Orthopaedics and Traumatology, 1996)
Femoral capital physeal fractures have been successfully repaired with 7.0 mm stainless steel cannulated screws. The holding power of 7.0 mm stainless steel cannulated screws, 8.0 mm stainless steel cannulated screws and 8.0 mm titanium cannulated screws was compared. The 8.0 mm titanium cannulated screw had the highest holding power, the 7.0 mm stainless steel cannulated screw was intermediate and the 8.0 mm stainless steel cannulated screw had the lowest holding power.When placed in the bovine femoral head, 8.0 mm titanium cannulated screws have holding power greater than 8.0 mm stainless steel cannulated screws. A 7.0 mm stainless steel cannulated screw has intermediate holding power.
Keywords: Cannulated screw; holding power; femoral capital physeal fracture